Lactiplantibacillus plantarum NMGL2 exopolysaccharide ameliorates DSS-induced IBD in mice mainly by regulation of intestinal tight junction and NF-κB p65 protein expression - Zhou, Zengjia; Zhang, Min; Yao, Mengke; Naseeb, Jasra; Sarwar, Abid; Yang, Zhennai; Aziz, Tariq; Alhomrani, Majid; Alsanie, Walaa F.; Alamri, Abdulhakeem S. (Frontiers in Microbiology, 2024)
Treatment of inflammatory bowel disease (IBD), a common chronic intestinal disease, by exopolysaccharides (EPSs) produced by lactic acid bacteria has raised increasing concerns. Here, the EPS produced by Lactiplantibacillus plantarum NMGL2 was evaluated for its ameliorating effect on dextran sodium sulfate (DSS)-induced IBD in mice. Administration of the EPS was shown to decrease the body weight loss and the values of disease activity index (DAI) and alleviate the colon damage as evidenced by an improvement in colonic length shortening, a reduction in colonic coefficient, and a reduction in colonic mucosal architecture and inflammatory infiltration. Cytokine assay of the blood and colon tissue samples showed that the EPS could decrease the levels of pro-inflammatory TNF-α and IL-1β, and increase anti-inflammatory IL-10.Oxidative stress assay of the colon tissue showed that the nitric oxide (NO) and malondialdehyde (MDA) levels decreased significantly (P < 0.05), while superoxide dismutase (SOD) and glutathione (GSH) levels increased significantly (P < 0.05) after the EPS intervention. These results were further confirmed by the significantly (P < 0.05) down-regulated levels of NF-κB p65, p-IKKβ, and p-IκBα, and significantly (P < 0.05) enhanced expression of ZO-1 and occludin, as evaluated by Western-blot analysis of these proteins expressed in colonic tissue. The EPS produced by L. plantarum NMGL2 alleviated IBD by suppressing the NF-κB signaling pathway, suggesting its potential as a functional food agent in the prevention of IBD.